Numerical simulation and experimental validation of microwave torrefaction for empty fruit bunches pellet - Yek, Peter Nai Yuh; Mohd Shahril Osman,; Kong, Sieng Huat; Law, Ming Chiat; Liew, Rock Keey; Lam, Su Shiung (Penerbit Universiti Kebangsaan Malaysia, 2019)
This study investigates the microwave heating and torrefaction process of empty fruit bunch (EFB) pellets. Finite element based COMSOL Multiphysics software was used to predict the microwave heating behaviour of EFB pellets during the torrefaction process. The simulated temperature data from multimode microwave system at 2.45 GHz frequency was used to compare and validate the experimental results. Quantitative validation of 10 min temperature profiles between 25-300 °C was performed by comparing the simulated and experimental results. RMSE and maximum different temperature profile were 16.42 and 38°C respectively which may cause by the moisture of pellet, exothermic reaction and placement of the thermocouple during microwave torrefaction process. The simulation work has successfully identified the hot spots of EFB pellets during microwave torrefaction. Hot spot happened in the temperature range of 250-450 °C and was observed near the waveguide and centre of the EFB pellets bed. This study provided a framework and required model parameters to predict temperature profile and hot spot location for a specific geometry of microwave cavity.